Prescribing and deprescribing in very old age: perceptions of very old adults, caregivers and health professionals. (14th November 2022) - Ouellet, Nicole; Bergeron, Anne-Sophie; Gagnon, Eric; Cossette, Benoit; Labrecque, Cory A; Sirois, Caroline
Abstract: Background: although they are major consumers of medications, there is little evidence-based data to guide prescribing and deprescribing of medications for very old adults (80+ years). Objectives: to discover the perceptions of very old adults, caregivers and health professionals in order to further examine the clinical and ethical issues raised by prescribing and deprescribing in very old age. Methods: individual interviews were conducted with very old adults ( n  = 10) and caregivers ( n  = 6), whereas group interviews were conducted with health professionals ( n  = 11). The themes covered included perceptions of medication use, polypharmacy, deprescribing and patient-health professional relationships. Thematic analysis was used to identify areas of convergence and divergence. Results: very old adults are satisfied with the medications they are taking, do not see the need to reduce their medication use and consider their doctor as the expert who should make the decisions regarding treatment. The perceptions of caregivers are similar to those of older adults, whereas health professionals believe that very old adults take a lot of inappropriate medications and list multiple barriers to deprescribing. All participants describe a normalisation of medication use with ageing. Conclusion: there is a dichotomy between the perception of the very old adults/caregivers and that of health professionals regarding the safety of medication in very old age. A cultural change regarding medication use seems essential to optimise therapy and support deprescribing in clinical practice since the potential issues raised by researchers do not resonate with the main stakeholders.